UI/UX Design of Stunting Survey Application Prototype User Centreed Design Method - Pawenrusi, Esse Puji; Kamariana, Kamariana; Kasma, Andi Yulia; Wahyuni, Eka; Aman, Andryanto (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The purpose of this research is to design UI/UX prototype of the stunting survey application according to user needs, namely (a) users can manage family data, (b), manage prospective bride data, (c) users can input questionnaire data, (d) search data, (e) see evaluation of questionnaire survey results, and (f) users can see the coordinate points of the survey results. The method used in the research is User Centered Design (UCD) which consists of 4 stages, namely Understand context of use, Specify user requirements, Design solutions, Evaluate against requirements. This research successfully designed the design and prototype of a stunting survey application that focuses on user needs and convenience. The prototype testing scenario was carried out with 2 experts who each have expertise in the field of UI/UX Designers and in the field of Public Health, the test results showed that the application interface was well received by the testers, and most tasks could be completed smoothly. This shows that the stunting survey application prototype has been made according to user needs, functional suitability, and easy to navigate by users. The results of this research are expected to be implemented in the actual environment so as to get feedback from users, in this case public health officers as surveyors.